Clinical-biochemical substantiation of reosorbilact application at brain injuries associated with extremities’ bones fractures - Ivanyushko, O. V. (Ukrainian Neurosurgical Journal, 2008)
The results of investigation of 96 victims with brain injuries (52 of them — with associated and 44 — with isolated brain trauma) were presented. It was established that at associated brain trauma the breaks of hemodynamics, heavy blood loss, and endotoxicosis were more expressed. Reosorbilact (polyatomic alcohol on the base of sorbitol) application is the effective method for hemodynamics normalization and intoxication syndrome removing.